An Assessment of the Materials and Methods Used in Disseminating Information on Human Trafficking among Residents of Two Barangays in Quezon City - Tojos, Leticia S. (Philippine Journal of Social Development, 2011)
Given the importance of popularizing human trafficking as a human rights issue, this study looks into the initiatives of local officials and non-government organizations in Barangays Botocan and Escopa 3 in Quezon City   to disseminate information among residents .   The assessment covered the following areas : messages or content of the materials,   methods and media for disseminating information, consumers and extent of dissemination, and effects on   receivers of   information.   Data gathering was done by reviewing available   information dissemination materials, interviewing key informants, and   conducting focus group discussion with selected residents.   Findings show that the Quezon City government has a number of instructive materials on human trafficking that have targeted its social workers and other frontline service providers, and   barangay officials and residents.   The materials promote the human rights perspective.     However, the contents or messages have not been fully understood by   barangay   residents.   Methods of dissemination have also not facilitated comprehension and retention of information. This was because human trafficking as a topic was only one among several inputs to the barangays without benefit of discussion.   Positive outcomes of the efforts include   the improved handling of human trafficking cases   by direct service workers and local officials as well as reporting of cases by residents.